2015
DOI: 10.1186/s12913-015-1105-8
|View full text |Cite
|
Sign up to set email alerts
|

Equity impact of a choice reform and change in reimbursement system in primary care in Stockholm County Council

Abstract: BackgroundIn 2008 reforms were introduced in primary care in Stockholm County Council to increase patient choice. These reforms included changes to the reimbursement system from one that was primarily based on need-weighted capitation system (75 %) to a system largely based on fee-for-service (60 %) and freedom of establishment of primary care clinics. The new reimbursement system created incentives for producing many visits and additional primary care clinics were established, particularly in areas that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
(21 reference statements)
2
27
0
Order By: Relevance
“…These findings are consistent with those of studies showing that the introduction of primary care workers would increase health care utilization and outpatient visits at PHCs among patients with chronic diseases . In addition, studies in Sweden and Mexico have both indicated that government financial investment in PHCs can increase the number of visits to these facilities …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with those of studies showing that the introduction of primary care workers would increase health care utilization and outpatient visits at PHCs among patients with chronic diseases . In addition, studies in Sweden and Mexico have both indicated that government financial investment in PHCs can increase the number of visits to these facilities …”
Section: Discussionsupporting
confidence: 90%
“…16,30,31 In addition, studies in Sweden and Mexico have both indicated that government financial investment in PHCs can increase the number of visits to these facilities. 20,21 Second, the positive association between ARR at county hospitals and the probability of visiting those hospitals was stronger in areas with higher physician densities in the county hospitals. This finding has some implications for targeted health insurance improvement and health workforce allocation strategies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…no. Year Area(s) Data Focus Results Scientific articles Beckman, Anell [ 23 ] 2013 Region Skåne Population register data Process of care – PHC visits Visits increased more among high-income than low income earners Agerholm et al [ 25 ] 2015 Stockholm County council Population register data, public health survey data Process of care – PHC visits Visits increased more among person with lesser needs; less among those with greater needs Glenngård [ 32 ] 2013 Region Halland, Skåne, Västra Götaland Patient survey data Outcome – Patient satisfaction Satisfaction with primary care higher in areas with low level of social deprivation and in smaller practices Maun et al [ 27 ] 2013 Gothenburg Interviews with 24 PHC managers Process of care – doctors’ views Prioritisation conflicts among doctors between patients with different needs and demands. Chronically ill patients were crowded out.…”
Section: Resultsmentioning
confidence: 99%
“…Sweden has a universal, comprehensive, and mainly tax‐financed health care system in which services should be accessed based on need, regardless of economic or social resources, although studies have shown that this objective has not been fully reached (e.g., Agerholm et al. ). Copayments exist, but are small (≈4 percent), and those with extensive health care needs are covered by a national high‐cost protection (ceiling set at SEK 1,100, after that no further charges for the remainder of the 12‐month period).…”
mentioning
confidence: 99%